The Influence of Transformational Leadership and Work Environment on Teacher Performance through Motivation as a Mediating Variable at SMA NEGERI Pasaman Regency - Rahmi Saleh; Lusi Susanti; Syahril; Merika Setiawati (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study examines the relationships between transformational leadership, work environment, teacher motivation, and teacher performance in public senior high schools in Pasaman Regency. A quantitative approach with an ex post facto causal-associative design was employed. The study involved 230 ASN teachers selected from a population of 495 teachers across 12 public senior high schools using proportional stratified random sampling. Data were collected through a five-point Likert-scale questionnaire measuring transformational leadership, work environment, motivation, and teacher performance. The data were analyzed using descriptive and inferential procedures to assess direct and indirect relationships among the variables. The findings indicate that transformational leadership contributed 48.1% to teacher motivation and 58.1% to teacher performance, while work environment contributed 51.4% to motivation and 54.4% to teacher performance. Motivation contributed 46.8% to teacher performance. The findings further indicate that motivation functions as a mediating variable in the relationships between transformational leadership and teacher performance and between work environment and teacher performance. These results demonstrate that teacher performance is influenced not only by leadership and workplace conditions but also by the motivational processes through which these organizational factors operate. The study highlights the importance of integrating transformational leadership, a supportive work environment, and sustained efforts to strengthen teacher motivation as part of school-based strategies for improving teacher performance.